2012
DOI: 10.1098/rstb.2011.0272
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of stomatal density influences stomatal size, plant growth and tolerance to restricted water supply across a growth carbon dioxide gradient

Abstract: To investigate the impact of manipulating stomatal density, a collection of Arabidopsis epidermal patterning factor (EPF) mutants with an approximately 16-fold range of stomatal densities (approx. 20–325% of that of control plants) were grown at three atmospheric carbon dioxide (CO 2 ) concentrations (200, 450 and 1000 ppm), and 30 per cent or 70 per cent soil water content. A strong negative correlation between stomatal size ( S ) and sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
245
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(278 citation statements)
references
References 44 publications
29
245
2
2
Order By: Relevance
“…3). An inverse correlation between size and density of stomata has been also noted by Doheny-Adams et al (2012) in Arabidopsis. In the same study, a less adverse effect of reduced water availability was observed on plants with lower stomatal density, which corresponds well with our results.…”
Section: Discussionmentioning
confidence: 59%
“…3). An inverse correlation between size and density of stomata has been also noted by Doheny-Adams et al (2012) in Arabidopsis. In the same study, a less adverse effect of reduced water availability was observed on plants with lower stomatal density, which corresponds well with our results.…”
Section: Discussionmentioning
confidence: 59%
“…Changes in D appear to be inextricably linked to changes in S, and it is the combination of S and D that determines g c(max) and g w(max) . There is a consistent negative relationship between S and D at all scales, including leaves within a single species (Franks et al, 2009), across species in a population (Hetherington and Woodward, 2003;Russo et al, 2010), through the fossil record (Franks and Beerling, 2009b), and across mutants of a single species where D is induced to vary by genetic manipulation (Doheny-Adams et al, 2012;Dow et al, 2014;Franks et al, 2015). This negative logarithmic relationship (often represented as a negative linear log-log plot) fundamentally constrains the adaptation and evolution of stomata under forcing by any environmental variable affecting leaf gas exchange.…”
Section: Stomatal Size Density and Conductance Through Deep Timementioning
confidence: 94%
“…As stomatal density has been correlated with g s (Franks and Beerling, 2009), the rationale behind manipulating stomata anatomical characteristics to increase or decrease stomatal density may be considered relatively straightforward, helped by studies that have illustrated that manipulation of a single gene can alter stomatal patterning (Doheny-Adams et al, 2012). However, the manipulation of stomatal functional responses is clearly more complicated.…”
Section: Stomatal Densitymentioning
confidence: 99%
“…It is noteworthy that the strong correlation between stomatal density and size was maintained within these plants: plants with lower stomatal densities also showed a greater mean stomatal size, whereas smaller stomata were found in leaves with greater stomatal densities. Interestingly, those plants with reduced density and larger stomata also showed reduced transpiration, greater growth rates, and a larger biomass (Doheny-Adams et al, 2012). The authors ascribed the improved growth rate to a combination of improved water status, higher metabolic temperatures, and lower metabolic costs associated with the development of guard cells.…”
Section: Stomatal Anatomymentioning
confidence: 99%